THE IMPORTANCE OF IMPLEMENTING COMPOSTING WITHIN COMPANIES FOR WASTE MANAGEMENT - ORGANIC BIOTECH CASE STUDY - Novais da Silva , Fernando; Zimmermann , Guilherme; Prim , Pâmela; Amaral Reinert , Kamili (Revista Gênero e Interdisciplinaridade, 2025)
The urgency of promoting sustainability in productive systems, particularly in waste management, has become a global priority. Sustainable Development Goal (SDG) 12.3 aims to halve global per capita food waste by 2030 (United Nations, 2025). In this context, the composting of organic waste emerges as a crucial alternative for mitigating the environmental impact associated with inadequate landfill disposal, while aligning with ESG (Environmental, Social, and Governance) principles and the Circular Economy (CE) framework (Li et al., 2021). This scientific article analyzes the strategic relevance of in-company composting, highlighting Organa Biotech—a startup based in Joinville (SC)—as a pioneering case study. Organa Biotech employs biotechnology and gravimetry to conduct precise diagnostics and accelerated treatment of organic waste on-site, transforming it into high-quality compost and providing the necessary evidence (facts, data, and information) for companies to complete ESG reports and demonstrate the effectiveness of their sustainable practices. The adoption of these practices not only reduces waste but also promotes decarbonization, generates economic value, and strengthens competitive advantage. This work was supported by the Fundação de Amparo à Pesquisa e Inovação do Estado de Santa Catarina (FAPESC), through Public Call No. 50/2024 – Programa Impulsiona SC.